Understanding the Nepali Classroom Practices: A Constructivist Perspective - Bhattarai, Devi Prasad; Basnet, Hom Bahadur (Journal of Research and Development, 2022)
This article concerns pedagogical practices of schools to meet objectives of the curriculum and provide learning experiences to the students. This article aims to explore teachers’ ways of carrying out classroom practices and to locate how the constructivist perspective could foster wider learning experiences of learners. We conducted an ethnographic field study - in one of the schools located in Ithaki Sub-metropolitan, Sunsari district – which involves a three-day visit to the school and continuous observation of a particular class to generate the data. Theoretically, this paper focuses on the constructivist perspective to understand the classroom practices of school teachers and locate them to conceptualize the school pedagogy. We highlight that the current school practice, the school teachers are adopting, is a traditionally dominant approach that strongly upholds “the jug to the mug concept” – the teacher as a jug that pours knowledge and information as a form of water to an empty mug as a student. We argue that teachers' traditionally based classroom practice is one of the responsible factors for not shifting Nepalese classroom practices into student-centered or reciprocal classroom practices that embrace the constructivist paradigm. This paper unveils teacher-student power-relations, which is fueling to promote the traditionally focused classroom practices that undermine the possibility of multiplicity in knowledge construction.